Structured platform-aware programming for Rust - Carvalho-Junior, Francisco Heron de; Nogueira, José Mykael Alves; Alencar, João Marcelo Uchôa de (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2025)
Structured platform-aware programming provides performance engineers with the ability to develop optimized function variants that exploit specific features of target execution platforms in a modular way. In this paper, we introduce and evaluate an approach for structured platform-aware programming with Rust, a systems programming language that has gained attention in HPC.